Erodibility of Granular Materials Models - Ari Sentani; Didier Marot; Fateh Bendahmane (Universitas Islam Sultan Agung, 2018)
Abstract: Two means physical processes are involved in failure of a dams structure: either a mechanical failure by sliding, or a hydraulic failure by erosion. The causes of failures are internal erosion (23 cases between 44), or external erosion (20 cases of overtopping) and 1 case of sliding. In consequence, internal erosion is the most frequent cause for all the water retaining structures. A series of test are needed to develop models that can describe the internal erosion. This research uses two kinds of tests. They are The Consodilated Drained (CD) Triaxial test and The Erodibility test with triaxial erodimetre. These two tests uses mixture between Kaolinite Proclay (25%) and Fontainebleau Sand (75%) with 9% of water content. The result shows that confinement pressure increase, time for obtained maximal deviatoric also increase. When deviatoric stress is increase, percentage of deformation is also increase. And also the volume variation of specimen is decrease in function of deformation. For the second test, the result shows after the loss of fine particles in the soil, the original dilative stress-strain behavior changes to be contractive and the peak stress is decreases. Comparing the results of Chang & Zhang in 2011, the curves rank in a coherent way for the stress-strain curve although it used different speciments.